Association of tattooing and hepatitis C virus infection: A multicenter case‐control study12. Issue 6 (12th June 2013) - Carney, Kerrilynn; Dhalla, Sameer; Aytaman, Ayse; Tenner, Craig T.; Francois, Fritz
Abstract Although injection drug use (IDU) and blood transfusions prior to 1992 are well‐accepted risk factors for hepatitis C virus (HCV) infection, many studies that evaluated tattooing as a risk factor for HCV infection did not control for a history of IDU or transfusion prior to 1992. In this large, multicenter, case‐control study, we analyzed demographic and HCV risk factor exposure history data from 3, 871 patients, including 1, 930 with chronic HCV infection (HCV RNA–positive) and 1, 941 HCV‐negative (HCV antibody–negative) controls. Crude and fully adjusted odds ratios (ORs) of tattoo exposure by multivariate logistic regression in HCV‐infected versus controls were determined. As expected, IDU (65.9% versus 17.8%; P < 0.001), blood transfusion prior to 1992 (22.3% versus 11.1%; P < 0.001), and history of having one or more tattoos (OR, 3.81; 95% CI, 3.23‐4.49; P < 0.001) were more common in HCV‐infected patients than in control subjects. After excluding all patients with a history of ever injecting drugs and those who had a blood transfusion prior to 1992, a total of 1, 886 subjects remained for analysis (465 HCV‐positive patients and 1, 421 controls). Among these individuals without traditional risk factors, HCV‐positive patients remained significantly more likely to have a history of one or more tattoos after adjustment for age, sex, and race/ethnicity (OR, 5.17; 95% CI, 3.75‐7.11; P < 0.001). Conclusion: Tattooing is associated with HCV infection, even among those without traditional HCV risk factors such as IDU and blood transfusion prior to 1992. (HEPATOLOGY 2013;57:2117–2123)